2017
DOI: 10.3390/ma10020143
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Storage Density and Impedance Response of PLZT2/95/5 Antiferroelectric Ceramics

Abstract: (Pb 0.97 La 0.02 )(Zr 0.95 Ti 0.05 )O 3 (PLZT2/95/5) ceramics were successfully prepared via a solid-state reaction route. The dielectric properties were investigated in the temperature region of 26-650 • C. The dielectric diffuse anomaly in the dielectric relaxation was found in the high temperature region of 600-650 • C with increasing the measuring frequency, which was related to the dynamic thermal process of ionized oxygen vacancies generated in the high temperature. Two phase transition points were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The characteristic temperatures of T o decreased, whereas T C increased. 14 The temperature of the FE-AFE phase transition, Curie temperature and maximum relative permittivity were shown in Table 1. With lead excess content 10% and 15%, the small anomalous peak T o was wide humps, which could be the phase tetragonal AFE phase and rhombohedral FE phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristic temperatures of T o decreased, whereas T C increased. 14 The temperature of the FE-AFE phase transition, Curie temperature and maximum relative permittivity were shown in Table 1. With lead excess content 10% and 15%, the small anomalous peak T o was wide humps, which could be the phase tetragonal AFE phase and rhombohedral FE phase.…”
Section: Resultsmentioning
confidence: 99%
“…(Pb 0.97(1+x) La 0.02 )(Zr 0.95 Ti 0.05 )O 3 ceramics with excess lead content (x ¼ 0, 3%, 5%, 7.5%, 10% and 15%) were successfully prepared via a solid-state reaction route. Compared with the previous study, 14 the experimental process used high purity lead oxide PbO and cold isostatic pressure technology. Raw materials of PbO (99%), TiO 2 (99%), ZrO 2 (99%) and La 2 O 3 (99.9%) were weighed according to the formula (Pb 0.97(1+x) La 0.02 )(Zr 0.95 -Ti 0.05 )O 3 in the required stoichiometry with different excess lead content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead-based antiferroelectric (AFE) ceramics have been studied and much progress has been made in the last few decades. (i) Through A-and B-site atom substitution, the critical AFE-ferroelectric (FE) transition field can be tailored; [10][11][12][13][14][15][16] (ii) Special sintering techniques have been adopted, such as hot-press and rolling processing, to improve microstructure and density, and both are believed to be efficient approaches for obtaining excellent energy storage properties in AFE ceramics. 17,18 The mechanism of energy storage in AFE involves the dipoles in AFE ceramics being antiparallel in arrangement and an electricfield induced AFE-FE transition utilized to store energy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in the investigation on the physical properties of (Pb 0.97 La 0.02 )(Zr 0.95 Ti 0.05 )O 3 (PLZT2/95/5) ceramics [11] revealed interesting behavior in the electric field dependence of polarization (P-E hysteresis loops) at different temperatures. Results have shown that the energy-storage density and efficiency achieved about 0.83 J/cm 3 and 70%, respectively, which is an improvement compared to the previous works [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%